Hubungan Penggunaan Buku Kia dengan Risiko Kejadian Stunting di Kecamatan Tandes Kota Surabaya - Bima, Ralvinzah Cahya Satriya; Irwanto, Irwanto; Aprilawati, Dwi (Universitas Pahlawan Tuanku Tambusai, 2024)
Stunting is a major nutritional problem that occurs in Indonesia and exceeds WHO standards, which are above 20 percent. Various factors support stunting and one of them is the utilization of Maternal and Child Health (MCH) books. The use of MCH books in Indonesia is still low, this is supported by the low utilization of MCH books by health workers which is only 2.2%. The purpose of the study was to determine the relationship between the use of the MCH book and the incidence of stunting that occurred in the Tandes District area of Surabaya City. The research design used was a Case Control study design. This research is a study by comparing the case group with the control group to see whether there is exposure or not. Group selection is done by selecting two groups, a group of mothers of toddlers with toddlers with good nutrition status (not stunted) associated with the use of MCH books as a control group and a group of mothers of toddlers with stunted toddlers associated with the use of MCH books as a case group (exposed group). The results showed that there were significant results on the completeness variable of the MCH book with a value of p = 0.049 with r = 0.249 and the variable of maternal monitoring of toddler development using the MCH book with a value of p = 0.000 with r = 0.933. The results of insignificant variables can be influenced by various factors such as limitations in determining measuring instruments for variables and various individual factors in the sample determined. The use of the MCH book has a significant relationship in the variable completeness of the MCH book and maternal monitoring of toddler growth using the MCH book to the incidence of stunting.